2020
DOI: 10.33899/ijvs.2020.126793.1382
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and some biochemical effects of platinum drug on the liver and kidney of pregnant mice Mus musculus and their embryos

Abstract: The current study was done to investigate the effects of two doses 3and 6 mg/kg B.w. of the Platinum drug on the structure of the liver and kidney of pregnant mice, and embryos in addition to the weight of the mothers, embryos, maternal liver and kidneys, as well as some biochemical parameters, were established. For this study, thirty pregnant mice were used, divided into three groups (10 mice/group) as follows; group I (control group); animals were injected intraperitoneally (IP) with distilled water on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Askaripour et al (16) mentioned that the gonadotrophiclike effects of many herbal extracts can perform many biological actions, including elevated ovarian and uterine relative weight, induction of ovulation, and stimulation of steroidogenic and protein biosynthesis pathways. Moreover, it has been stated that the natural antioxidants of herbal sources have a modulatory effect to treat abnormal hormone secretions accompanying with oxidative stress (17), where the previous findings revealed potent activity of silymarin as an antioxidant which could directly scavenge the increased free radicals caused by EtBr repro-toxicity, inactivate them, and repair the damage (18). Furthermore, this result might be attributes to the role of silymarin to increase ovarian estrogen production, as ovarian sex hormones (estradiol and progesterone) work together in a precise and coordinated mechanism in the control of ovarian functions, including folliculogenesis, oogenesis, the estrous cycle, sexual behavior and ovulation, as the biosynthesis and action of the hormones can be modified by endogenous and/or exogenous factors (19).…”
Section: Discussionmentioning
confidence: 99%
“…Askaripour et al (16) mentioned that the gonadotrophiclike effects of many herbal extracts can perform many biological actions, including elevated ovarian and uterine relative weight, induction of ovulation, and stimulation of steroidogenic and protein biosynthesis pathways. Moreover, it has been stated that the natural antioxidants of herbal sources have a modulatory effect to treat abnormal hormone secretions accompanying with oxidative stress (17), where the previous findings revealed potent activity of silymarin as an antioxidant which could directly scavenge the increased free radicals caused by EtBr repro-toxicity, inactivate them, and repair the damage (18). Furthermore, this result might be attributes to the role of silymarin to increase ovarian estrogen production, as ovarian sex hormones (estradiol and progesterone) work together in a precise and coordinated mechanism in the control of ovarian functions, including folliculogenesis, oogenesis, the estrous cycle, sexual behavior and ovulation, as the biosynthesis and action of the hormones can be modified by endogenous and/or exogenous factors (19).…”
Section: Discussionmentioning
confidence: 99%
“…Heart sections in rat treated with 10 and 20 mg/kg DMH shows edema, Zenker's necrosis, discontinuation of muscle fibers with foci of infiltration of inflammatory cells and hemorrhage but more sever lesions in dose 20 mg/kg some studies indicated that there are a vasoconstriction occur in the coronary vessels of heart after Acute exposure to DMH (20), heart lesions occurs because of toxic effect of DMH and free radicle that release whereas DMH needs bio activations to induce its mutagenic effects and induce its hepatotoxic effects so its activated metabolically in liver by several steps of reactions to carcinogenic and toxic metabolite through intermediates methylazoxymethanol and azoxymethane and these metabolite affect cardiac muscles and cause cardiomyopathies (18,36,37).because of DMH is a potent colonic and hepatic carcinogen many tumors that occur in colon cause release of H2O2 which is under go detoxification in liver and distributed in all tissues by circulation including heart and many generations of H2O2 are produced from this tumors thus induce cardiomyopathies and continuous injury to rat tissues (38,39). Kidneys sections in rats treated with10 and 20 mg/kg DMH for 8 weeks reveals vacuolar degeneration of epithelial lining renal tubules with cloudy swelling and hyaline casts in some lumen of renal tubules because of application of hydrazine derivates is nephrotoxic and leads to an impairment in renal tubules, decreasing glomerular filtration rate and function (11,40,41), a numbers of animals studies on hydrazine and it derivatives are hypothesized that toxicity is exerted by interfering in urea cycle this occurred by increased levels Nα-acetyl citrulline and arginosuccinate (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 25 adult Swiss female mice were used to achieve comparison between control group and pregnant and non-pregnant mice. The mice were placed under conditions of temperature 20-25ºC and 12 hours of darkness, 12 hours of light (10).…”
Section: Animals and Experimental Designmentioning
confidence: 99%